Managing globalization : lessons from China and India - Kelly, David A. (ed.); Rajan, Ramkishen S. (ed.); Goh, Gillian H.L. (ed.) (New Jersey, 2006)
The dynamics of a global economy is being reshaped by the economic emergence of two Asian giants, China and India. How the world's two most populous countries manage globalization as they pursue economic reform and liberalization will impact significantly their societies, the rest of Asia, and the world.This book brings together articles by first rate scholars of China and India to share and discuss their research findings in four areas: Challenges, Opportunities and Responses to Globalization; Social Security and Governance; National Security in the age of Globalization; and Ethnicity and Identity in the New World.The book includes an opening address by Singapore's Minister Mentor Lee Kuan Yew, from his speech on (3z(BManaging Globalization: Lessons from China and India(3y(B, delivered at the official opening of the Lee Kuan Yew School of Public Policy on 4 April 2005.s
Keywords: Globalization-congresses